3a-6a+2a=-7a+y+5a

Simple and best practice solution for 3a-6a+2a=-7a+y+5a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-6a+2a=-7a+y+5a equation:


Simplifying
3a + -6a + 2a = -7a + y + 5a

Combine like terms: 3a + -6a = -3a
-3a + 2a = -7a + y + 5a

Combine like terms: -3a + 2a = -1a
-1a = -7a + y + 5a

Reorder the terms:
-1a = -7a + 5a + y

Combine like terms: -7a + 5a = -2a
-1a = -2a + y

Solving
-1a = -2a + y

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
-1a + 2a = -2a + 2a + y

Combine like terms: -1a + 2a = 1a
1a = -2a + 2a + y

Combine like terms: -2a + 2a = 0
1a = 0 + y
1a = y

Divide each side by '1'.
a = y

Simplifying
a = y

See similar equations:

| 4x^2+x=2 | | 7x+1x=8x+36+9x | | 3x+3-8=-4 | | 8x^2=34x-30 | | -10/-1.66 | | 6(3y-1)+2-(-3y+4)= | | N/-8-5=-12 | | 17x-7=7+10x | | -10/-5/3 | | 3(3x-7)=-2(8+3x) | | 3(3x-7)=-2(8+3x) | | -5=-8+v/10 | | a^2+49a=0 | | (x^2+7)/(3x^2-5)=0 | | (X+16)/3 | | a^2+49=0 | | 6(3y-1)+2-(-3+4)= | | 6m-5=-5m+7 | | 9+4t=6 | | 2x-(5x-7)-x=2(x+2)-8 | | 3x^2+18x+3=6 | | -5s^2+5s+9=0 | | 97+80+70+88+s=375 | | 5t-8=9t-10 | | 9=-6p+3/-8 | | -5a+16+3a=8a-6a | | 9-2x/7=5 | | a/2-10=a+20 | | 6x+2=16-x | | 9=-6+3/-8 | | 2(4-d)-5d=8 | | .4(x+70)+1.2x=92 |

Equations solver categories